The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11695-013-1104-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status 10 Years After Primary Gastric Bypass: Gravely High Prevalence of Hypovitaminosis D and Raised PTH Levels

Abstract: Vitamin D deficiency and secondary hyperparathyroidism after Roux-en-Y gastric bypass (RYGB) were confirmed in our study because 65 % of patients had vitamin D deficiency, and 69 % had increased PTH levels more than 10 years after surgery. These data are alarming and highlight the need for improved long-term follow-up. Vitamin D deficiency does not seem to progress with time after surgery, possibly due to weight loss. Only preoperative BMI, cutoff point 43 kg/m(2), was a predictor of vitamin D deficiency at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 29 publications
3
50
4
6
Order By: Relevance
“…37 The lower 25-hydroxyvitamin D concentrations than in our study could potentially be explained by a lower intake of vitamin D, with only 5% of patients reporting intake of vitamin D supplements. 37 A high deficiency rate of 25-hydroxyvitamin D in the long term after gastric bypass has been reported previously.…”
Section: Vitamin Concentrations After Gastric Bypass E Aaseth Et Alcontrasting
confidence: 52%
See 2 more Smart Citations
“…37 The lower 25-hydroxyvitamin D concentrations than in our study could potentially be explained by a lower intake of vitamin D, with only 5% of patients reporting intake of vitamin D supplements. 37 A high deficiency rate of 25-hydroxyvitamin D in the long term after gastric bypass has been reported previously.…”
Section: Vitamin Concentrations After Gastric Bypass E Aaseth Et Alcontrasting
confidence: 52%
“…37 The lower 25-hydroxyvitamin D concentrations than in our study could potentially be explained by a lower intake of vitamin D, with only 5% of patients reporting intake of vitamin D supplements. 37 A high deficiency rate of 25-hydroxyvitamin D in the long term after gastric bypass has been reported previously. 38,39 Despite vitamin D and calcium supplementation, we observed increased PTH 37,40 Perhaps the standard dose of 400 U vitamin D 3 is too low to prevent an increase in PTH concentrations in some patients.…”
Section: Vitamin Concentrations After Gastric Bypass E Aaseth Et Alcontrasting
confidence: 52%
See 1 more Smart Citation
“…Several studies used additional supplemental regimens in subjects who were deficient, as shown in Figure 3 and detailed in the Appendix. The timing of 25(OH)D status assessment also varied, from as early as 3 months [5868], to as late as 11 years post operatively [87]. …”
Section: Resultsmentioning
confidence: 99%
“…Bariatric surgery leads to anatomical and physiological alterations in gastro-intestinal tract that impairs absorption of some essential nutrients. Vitamin D and calcium, two fundamental factors in bone formation, are among the substances that their intestinal absorption is highly compromised (4). In this report we will describe a patient with severe hypocalcemia and osteomalacia after bariatric surgery needing emergency visit and admission.…”
Section: Introductionmentioning
confidence: 98%